Optical Fiber Multiparameter Detection and Numerical Simulation and Characteristics of Water Quality Particulate Matter Based on Single-Photon Detection Technology. (10th October 2022) - Xu, Quan; Gao, Cuiyun; Zhou, Chun
Abstract : Water quality testing is of great significance for daily water use or water use in high precision manufacturing. The use of single-photon detection technology to detect water particles is one of the important methods of physical water quality detection. However, the current water quality particle detection technology needs to be improved in the range and accuracy of turbidity detection. The paper aims to use single-photon detection technology to design a fiber optic turbidity detection system to solve the current problems of small turbidity detection range and low accuracy in a large range. In response to this, this paper has made an in-depth understanding of single-photon detection technology and designed two sets of detection schemes using the performance of photons. The first set is the transmission optical fiber turbidity detection, which can effectively detect the ultralow turbidity range and a wide range of water quality particles. The second set is a scattering optical fiber turbidity detection system, which can effectively detect water particles in the low and medium turbidity range. In this paper, the two systems were integrated into a whole system, so the results of the two detection methods can also be compared, and the detected turbidity can be obtained more accurately. The experimental results showed that for the transmission optical fiber turbidity detection system, the detection effect of the system was the best under the incident light intensity of 11 wm, and the fitting value was 0.99; for the scattering optical fiber turbidity detection system, the detection effect of the system was the best under the incident light intensity of 4 wm, and the fitting value was 0.99.